Molecularly imprinted SPE coupled with HPLC for the selective separation and enrichment of alkyl imidazolium ionic liquids in environmental water samples. Issue 19 (23rd August 2013) - Xia, Gao; Jing, Fan; Guifen, Zhu; Xiaolong, Wang; Jianji, Wang
<x xml:space="preserve">Abstract</x> A novel 1‐butyl‐3‐methylimidazolium chloride ionic liquid surface imprinted solid‐phase sorbent was synthesized. The as‐prepared material was characterized by SEM, Brunauer–Emmett–Teller surface area analysis and Fourier Transform IR measurements. Then its adsorption properties for alkyl imidazolium ionic liquids, including adsorption capacities, adsorption kinetics, and properties of selective separation and enrichment were studied in detail. It was shown that the ionic liquid surface imprinted polymer exhibited high selective recognition characteristics for the imidazolium chloride ionic liquids with short alkyl chains (CnmimCl, n = 2, 4, 6, 8) and the adsorption equilibrium was achieved within 25 min. Various parameters were optimized for the 1‐butyl‐3‐methylimidazolium chloride ionic liquid surface imprinted polymer SPE column, such as flow rate, eluent solvent, selectivity, and reusability of the column. Then, the SPE column coupled with HPLC was used for the determination of alkyl imidazolium ionic liquids. Experimental results showed that the existence of their structural analogs and common concomitants in environmental matrices did not affect the enrichment of 1‐butyl‐3‐methyl imidazolium chloride ionic liquid. The average recoveries of 1‐butyl‐3‐methylimidazolium chloride ionic liquid in spiked water samples were in the range of 92.0–102.0% with the RSD lower than 5.8%.